2020
DOI: 10.1210/clinem/dgaa927
|View full text |Cite
|
Sign up to set email alerts
|

MorbiNet Study: Hypothyroidism Comorbidity Networks in the Adult General Population

Abstract: Purpose Multimorbidity impacts quality of life. We constructed hypothyroidism comorbidity networks to identify positive and negative associations with other prevalent diseases. Methods We analyzed data of 285,342 patients with hypothyroidism from 3,135,948 adults with multimorbidity in a population-based study in Catalonia, Spain, (period: 2006-2017). We constructed hypothyroidism comorbidity networks using logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
4
0
1
Order By: Relevance
“…34,35 This mechanism may also explain the results in three other studies that describe the risk of poor prognosis related to NTIS in response to critical illness or the association between thyroid hormone levels and allcause mortality. 6,7,36 For participants with any known thyroid disease at baseline we identified a 30% increased risk for future 37,38 Even though we adjusted for many comorbid conditions, residual confounding is still possible. 39 A large population-based study found increased risk of infections with hypothyroidism the first year after baseline measurement of thyroid levels.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…34,35 This mechanism may also explain the results in three other studies that describe the risk of poor prognosis related to NTIS in response to critical illness or the association between thyroid hormone levels and allcause mortality. 6,7,36 For participants with any known thyroid disease at baseline we identified a 30% increased risk for future 37,38 Even though we adjusted for many comorbid conditions, residual confounding is still possible. 39 A large population-based study found increased risk of infections with hypothyroidism the first year after baseline measurement of thyroid levels.…”
Section: Discussionmentioning
confidence: 91%
“…Even if our timing of thyroid function measures was before sickness, we speculate that the increased BSI risk still could be a result of confounding by concurrent ill health, as we found no evidence of an association between TSH levels and BSI. Confounding by concurrent ill health can arise because chronically ill patients are more likely to be examined for thyroid disease and thus get the thyroid disease diagnosis while having other comorbid conditions that increase BSI risk 37,38 . Even though we adjusted for many comorbid conditions, residual confounding is still possible 39…”
Section: Discussionmentioning
confidence: 99%
“…For example, a comorbidity network for type 2 diabetes mellitus was visualised for pairs of conditions with OR > 1.2 and P-values for OR < 1e-5 [14]. Another study used OR > 1.2 or OR < 0.8 (for positive and negative associations) with P-values < 1e-5 to depict a comorbidity network of hypothyroidism in adults [15]. A comorbidity network for people living in rural Uganda was visualised for pairs of conditions which satis ed the following three conditions: RR > 1, Phi correlation > 0, and false discovery rate < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…For patients diagnosed with thyroid diseases, quality of life is also affected by the comorbid disorders. In relation to hypothyroidism, comorbid conditions include laryngeal cancer, congenital disorders, thyroid cancer, anemia with vitamin B12 or folic acid de ciency and goiter (40).…”
Section: Quality Of Life In Thyroid Patientsmentioning
confidence: 99%